(untitled) (Raparin Journal of Humanities (RJH), 2023)
Malai Gawra (Mala Mohammadi Koi) is the son of Mala Abdullah, the son of Mala Asaad, the son of Mala Abdulrahman whose family is known as (Jali Zada). He was born in Koya in 1876 and died in 1943. Through a brief look at the history of this family which takes more than 500 years we realize that they have played a great role and participated in social and political events of their time. During 67 years of Malai Gawra’s life he witnessed and took part in three different changes and historical stages such as, the end of Ottoman empire era (Abdul Hamid II, Itihad and Taraqi, the English invasion of Kurdistan and Iraq, and the monarchy era in Iraq; Faisal I and his son Ghazi). This study aims at analyzing the outlook and participation of Malai Gawra in the political matters and events of his era along with analyzing three foremost stages and political events he contributed in through analytical and descriptive methods.